Germania - Tacitus, Cornelius, 56-117; Hidén, K. J. (Karl Julius), 1867- (Salt Lake City, UT : Project Gutenberg, 2016)
"Germania" by Cornelius Tacitus is a historical and ethnographic work written around 98 AD. It describes the lands, laws, and customs of Germanic peoples living beyond the Roman Empire's borders. Tacitus examines their physical characteristics, government structures, gender roles, and tribal divisions, drawing from secondhand sources since he never visited the region himself. Rediscovered in 1425, this work profoundly influenced German humanism and later nationalist movements, shaping how Germanic antiquity was understood and interpreted throughout European history. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Germania_(book)
Release date is 2016-10-12
Produced by Tapio Riikonen
Keywords: Germanic peoples -- Early works to 1800